2020
DOI: 10.12973/eu-jer.9.3.1189
|View full text |Cite
|
Sign up to set email alerts
|

Involving Stakeholders in Shaping Educational Legislation and Policy in Ukraine

Abstract: The purpose of this research was to explore how effective the bottom-up approach to producing and shaping educational legislation is in Ukraine and to identify what observed changes take place in students if the bottom-up approach is simulated in the classroom. Qualitative instruments and observational data were used to yield the data. Those were a survey questionnaire, semistructured interview questionnaire, and focus group discussion observation checklists and moderators' and facilitators' reports. The data … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 26 publications
1
6
0
2
Order By: Relevance
“…Concerning governance, studies highlight the involvement of the stakeholders of higher education in strategic planning and policy-shaping. This has proven to be an alternative to the conventional law-making procedure in the sphere of education (Bobrytska et al, 2020). However, some studies express scepticism about the effectiveness and necessity of involving external stakeholders in the governance of institutions.…”
Section: Literature Reviewmentioning
confidence: 99%
See 4 more Smart Citations
“…Concerning governance, studies highlight the involvement of the stakeholders of higher education in strategic planning and policy-shaping. This has proven to be an alternative to the conventional law-making procedure in the sphere of education (Bobrytska et al, 2020). However, some studies express scepticism about the effectiveness and necessity of involving external stakeholders in the governance of institutions.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Graham et al (2012) contend that education crisis time is appropriate for fundamental curriculum development as institutions, educational systems, and instruction methods change owing to 'external shock'. Bobrytska et al (2020) found that this crisis has caused a shift from an input-based accreditation to an outcome-based scheme in higher education in Ukraine and that a new curriculum framework is needed.…”
Section: Literature Reviewmentioning
confidence: 99%
See 3 more Smart Citations